Answer:
its 48
Step-by-step explanation:
(x + 12) = (x + 14) - 3
subtract 12 from each side
x = x + 14 - 3 - 12
Now if we subtract x from each side we see that x - x = 0. Combine the terms left over and we have -1, so
0 = -1
The answer is NO SOLUTION
Answer:
Step-by-step explanation:
hello :
the vertex -form of quadratic function f(x) is : f(x) = a(x+b)²+c
the vertex : (- b , c )
means : (-2,-3) so : -b = -2 and c = - 3 so : b =2 and c = -3
f(x) = a(x+2)²-3
calculate : a
the graph passes through the point (2, 13) : f(2)=13
means : a(2+2)²-3 = 13
16a - = 13
16a = 16 so : a = 1
f(x) is represented by the equation f(x) = (x+2)²-3
The graph of f(x) color red and g(x) blue
is the y-intercept when g(x) greater g(x) than f(x) is when x=0 so : y = 6
The answer will be 60 because 8*8=64 then subtract 4